Viscoelastic properties of lower extremity muscles after elite track cycling sprint events: a case report - Klich, S.; Krymski, I.; Kawczynski, A. (Central European Journal of Sport Sciences and Medicine, 2020)
Sprint cycling events require a high level of anaerobic capacity and therefore may affect peripheral fatigue throughout exercise-induced muscle damage. In fact, those alterations might decrease power generation. This study was performed on a 23 years old elite track cyclist started in men`s sprint. The measurements included power output (W) and cadence (rpm), lactate concentration (La-), heart rate (bpm), Rated Perceived Exertion scale and viscoelastic properties analysis. The present study have shown a new approach to monitor the muscle properties of the lower extremity after 200m flying start and repeated sprint races. Therefore, we hypothesized that repeated sprint races might lead to alterations in viscoelastic properties of lower extremity muscles. In track cycling, especially sprint events these variations may lead to increasing muscle fatigue. Furthermore, training control and monitoring related to assessment of muscles properties can be a source of counteracting injuries and relieving fatigue.